Enhancing Second Language Speech: The Roles Of Task Repetition And Planning In Improving L2 English Production - Le, Nguyen Van Anh (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
This paper explores the impact of task repetition and planning conditions on the complexity, accuracy, and fluency (CAF) of second language (L2) speech production. By conducting a case study on an L2 English learner, the study investigates how the learner's speech performance is characterized under the CAF construct and how it is affected by task repetition, the absence of pre-task planning, and the presence of unpressured within-task planning. The study employs various measures to assess lexical and grammatical complexity, accuracy, and fluency. The findings suggest that while the lack of pre-task planning did not completely compromise complexity, accuracy remained low despite the unpressured within-task planning condition, and fluency was negatively impacted. However, task repetition led to improvements in all three dimensions of CAF. The paper concludes with pedagogical implications for L2 instruction, highlighting the importance of strategic and guided pre-task planning, multiple-task repetitions, and learner self-evaluation to enhance CAF in L2 speech production.